Diffuse alveolar hemorrhage in IgA nephropathy: case series and systematic review of the literature. (4th February 2016) - Rajagopala, Srinivas; Parameswaran, Sreejith; Ajmera, Jail Singh; Ganesh, Rajesh Nachiappa; Katrevula, Anudeep
Abstract: Objectives: To describe the spectrum of pulmonary involvement in immunoglobulin A nephropathy (IgAN). Methods: We describe two patients with pulmonary renal syndrome related to IgAN and a systematic review of previously reported cases of IgAN and lung involvement. Results: We identified 23 reports of IgAN‐related pulmonary disease, including 19 reports of alveolar hemorrhage and two cases of organizing pneumonia. Dyspnea (84%), hemoptysis (74%), cough (53%) and fever (47%) were common presenting complaints. Simultaneous involvement of kidneys and lung was the most common presentation (42%) but alveolar hemorrhage occurred independent of renal disease in one‐fifth (21%). Azotemia was seen in 55.5% at presentation. Mesangio‐proliferative glomerulonephritis was the most common biopsy finding and crescentic glomerulonephritis was seen in 27.7%. Among patients undergoing lung biopsy, capillaritis was seen in 72.7%; 37.5% of these had IgA deposits. Steroids with cyclophosphamide, followed by maintenance with methotrexate or azathioprine was used in 44%. Mechanical ventilation, dialysis and plasmapheresis were other adjunctive therapies used. IgAN‐related alveolar hemorrhage was associated with a mortality of 26.3% and significant morbidity, with 52.7% having end‐stage kidney disease despite immunosuppression. Organizing pneumonia with pulmonary IgA deposition is a well‐described association of IgAN. Conclusion: These findings are similar to our previous observations of Henoch–Schonlein purpura (HSP)‐related alveolar hemorrhage, highlighting the similarities of these related syndromes. Multicentric studies of IgAN and HSP‐related pulmonary renal syndrome with a standard protocol are needed to define their similarities and differences, optimum suppression and its role in preventing renal progression in this setting.